The Role of Affective Factors in the Process of Learning a Foreign Language by Late Adults - Grotek, Monika; Kiliańska-Przybyło, Grażyna (INSTED: Interdisciplinary Studies in Education & Society, 2012)
The article aims at describing the affective factors that accompany the process of foreign language learning by late adults aged: 53?83. The article also concentrates on such issues as motivation and language learning experiences as well as coping strategies implemented by late adults to minimize the negative affect. The research was carried out among 87 subjects (79 females and 8 males) who attended an English language course organized by the University of Third Age (Katowice) in 2011/2012. The research was based on a narrative inquiry and questionnaire data.